Sistem Informasi Rawat Inap Puskesmas Baktiya Kabupaten Aceh Utara - Novia Hasdyna, Muhammad Al Aziz Saputra, Rahmat, Yuswandi, Rahmati (LPPM-UNIKI, 2023)
The Baktiya Health Center is one of the health centers in Baktiya District, North Aceh Regency. The services offered by the Baktiya Health Center, as for complaints felt by the people of Baktiya District, are that there is no information regarding inpatient services, due to being the only health center in the District. Baktiya, so many people cannot use these inpatient services due to limited space or rooms for inpatients and information regarding room availability or room capacity at the Baktiya Health Center, and the process of data collection and information related to inpatient services is still done manually so slow down the performance of staff and officers at the Baktiya Health Center. For this reason, we need a system that functions to provide information about inpatient services at the Baktiya Health Center, to make it easier for staff and employees of the Health Center and the community to improve quality and services, especially inpatient services for the Baktiya Health Center. With the construction of a web-based Baktiya Health Center inpatient information system, it can help the community and Health Center staff to provide, receive and improve quality inpatient services at the Baktiya District Health Center.